The Effect of The Implementation of Green Banking, Capital Adequacy Ratio (Car), Bi 7-Days (Revers) Repo Rate and Exchange Rate on The Profitability of Banks Listed on The Indonesia Stock Exchange in The Period 2019-2023 - Indrasari, Peti; Mubarok, Abdullah; Susetyo, Budi; Indriasih, Dewi; Firmansyah, Fahmi; Astutie, Yanti Puji (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study aims to examine the influence of green banking implementation, capital adequacy ratio, BI 7-day (reverse) repo rate, and exchange rate on the profitability of banks listed on the Indonesian Stock Exchange. The research utilizes quantitative data derived from the annual financial reports of 19 purposefully selected banking companies, covering the period from 2019 to 2023. Through a specific sampling technique, a total of 95 observations were obtained. To analyse the relationship among variables, the study employed multiple linear regression analysis using SPSS version 22. The results reveal that both the capital adequacy ratio and the exchange rate have a significant effect on bank profitability. In contrast, the variables of green banking implementation and the BI 7-day reverse repo rate do not have a statistically significant impact on the profitability of the sampled banks during the observed period.